Centromere positioning orchestrates telomere bouquet formation and the initiation of meiotic differentiation - Alberto Jiménez-Martín; Alberto Pineda-Santaella; Rebeca Martín-García; Rodrigo Esteban-Villafañe; Alix Matarrese; Jesús Pinto-Cruz; Sergio Camacho-Cabañas; Daniel León-Periñán; Antonia Terrizzano; Rafael R. Daga; Sigurd Braun; Alfonso Fernández-Álvarez (Nature Communications)
Abstract Accurate gametogenesis requires the establishment of the telomere bouquet, an evolutionarily conserved, 3D chromosomal arrangement. In this spatial configuration, telomeres temporarily aggregate at the nuclear envelope during meiotic prophase, which facilitates chromosome pairing and recombination. The mechanisms governing the assembly of the telomere bouquet remain largely unexplored, primarily due to the challenges in visualizing and manipulating the bouquet. Here, using Schizosaccharomyces pombe as a model system to elucidate telomere bouquet function, we reveal that centromeres, traditionally perceived as playing a passive role in the chromosomal reorganization necessary for bouquet assembly, play a key role in the initiation of telomere bouquet formation. We demonstrate that centromeres are capable to induce telomere mobilization, which is sufficient to trigger the first stages of bouquet assembly and the meiotic transcription program in mitotic cells. This discovery highlights the finely tuned control exerted over long-distance heterochromatic regions and underscores a pivotal step in the mechanism of eukaryotic telomere bouquet formation and meiotic transcriptional rewiring.